Pengaruh Hipnotis Lima Jari terhadap Tingkat Kecemasan dalam Menghadapi Kematian pada Lansia - Maharani, Putri Sri; Tresya, Elvie; Safitri, Aisyah (MPI Press, 2024)
Introduction: Anxiety about the death of the elderly is an emotional condition felt by the elderly when they think about death. Objectives: To determine the influence of five-finger hypnosis on the level of anxiety in facing death in the elderly in KP. Cilangkap RT 02 RW 17 in 2022 Method: This research uses quantitative research with the type of experimental research using a pre-experimental Design. The design carried out is a one group pretest-posttest research design. The population in this study was 45 elderly people in RT 02 RW 017. The sampling technique used probability sampling with a total of 25 respondents. The research tool for collecting data used a questionnaire sheet on the Geriatric Anxiety Scale (GAS) anxiety measurement scale, then a normality test was carried out using the Shapiro-Wilk test and an influence test using the Wilcoxon test. Result: Research using the Wilcoxon test showed the effect of five-finger hypnosis on anxiety levels in facing death with a p-value of 0.002 < 0.05. Conclusion: There is an influence of five-finger hypnosis on the level of anxiety in facing death in the elderly in KP. Cilangkap RT 02 RW 17 in 2022